2022
DOI: 10.1111/jonm.13696
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a group‐based acceptance and commitment therapy programme on the mental health of clinical nurses during the COVID‐19 sporadic outbreak period

Abstract: Aim To develop and implement of a group‐based acceptance and commitment therapy programme in helping clinical nurses with mental health problems during the sporadic COVID‐19 outbreak period. Background In the face of the continuing COVID‐19 pandemic, clinical nurses have a high risk of mental health issues. Methods A quasi‐experimental design was used. Two hundred twenty‐six nurses were recruited from four general hospitals to receive 10 sess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…To our knowledge, this study is the rst to investigate multi-dimensional sleep patterns in primary HCWs during the rst wave of the 2022 COVID-19 pandemic in Shanghai. Other studies in China have generally focused on sleep as a secondary component of overall mental health (3) or speci c provider groups, such as HCWs from tertiary medical centers (20), intensive care units (ICU) practitioners (21), nurses (22), and anesthesiologists (23). Hassinger (5) et al investigated sleep patterns of all frontline and non-frontline providers using various sleep dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this study is the rst to investigate multi-dimensional sleep patterns in primary HCWs during the rst wave of the 2022 COVID-19 pandemic in Shanghai. Other studies in China have generally focused on sleep as a secondary component of overall mental health (3) or speci c provider groups, such as HCWs from tertiary medical centers (20), intensive care units (ICU) practitioners (21), nurses (22), and anesthesiologists (23). Hassinger (5) et al investigated sleep patterns of all frontline and non-frontline providers using various sleep dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…17 Despite the widely established negative mental health effects of the pandemic on HCWs, little published work has examined mental health interventions for HCWs during the COVID-19 pandemic. In general, existing studies suggest that brief interventions focused on improving HCWs' mental health during COVID-19 were associated with reductions in anxiety, [18][19][20][21][22][23] depression, [18][19][20][21] stress, 22,24 and sleep disturbance, 19 while others found no changes in anxiety, 25,26 depression, 25 stress, [25][26][27] and insomnia. 21,25 The interventions used included resilience enhancement, [22][23][24]28 cognitive behaviour therapy (CBT), 18,20,21 acceptance and commitment therapy, 27 and mindfulness.…”
Section: Introductionmentioning
confidence: 99%
“…In general, existing studies suggest that brief interventions focused on improving HCWs' mental health during COVID-19 were associated with reductions in anxiety, [18][19][20][21][22][23] depression, [18][19][20][21] stress, 22,24 and sleep disturbance, 19 while others found no changes in anxiety, 25,26 depression, 25 stress, [25][26][27] and insomnia. 21,25 The interventions used included resilience enhancement, [22][23][24]28 cognitive behaviour therapy (CBT), 18,20,21 acceptance and commitment therapy, 27 and mindfulness. 19,[25][26][27] Many of the aforementioned studies had small sample sizes, were conducted outside of North America, and started months to over a year after the pandemic onset.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance, there is currently no standardized psychological intervention model aimed at healthcare workers in situations of infectious diseases; however, the available digital interventions have been directed towards reducing emotional distress and promoting positive aspects [20]. Approaches such as CBT [19,21,[24][25][26][27], behavioral activation (BA) [17], acceptance and commitment therapy (ACT) [28], mindfulness, yoga, music therapy and progressive relaxation [21,22,24,25], resilience [17,20,22,24], self-care, social support [22], as well as positive psychology (PP) techniques to increase mental well-being, mental toughness and gratitude [18] have been applied for healthcare workers during the COVID-19 pandemic. In addition, the systematic reviews identified that part of the objectives of the interventions were to promote well-being, quality of life and self-efficacy [19], using: psychological first aid (PFA); eye movement desensitization and reprocessing (EMDR); anticipate, plan, and deter (APD); resilience at work (RAW); resilience and coping for the healthcare community (RCHC) and trauma risk management (TRiM)) [20].…”
Section: Introductionmentioning
confidence: 99%